Xenon as an adjuvant to sevoflurane anesthesia in children younger than 4 years of age, undergoing interventional or diagnostic cardiac catheterization: A randomized controlled clinical trial. Issue 12 (5th September 2017) - Devroe, Sarah; Meeusen, Roselien; Gewillig, Marc; Cools, Bjorn; Poesen, Koen; Sanders, Robert; Rex, Steffen
Summary: Background: Xenon has repeatedly been demonstrated to have only minimal hemodynamic side effects when compared to other anesthetics. Moreover, in experimental models, xenon was found to be neuroprotective and devoid of developmental neurotoxicity. These properties could render xenon attractive for the anesthesia in neonates and infants with congenital heart disease. However, experience with xenon anesthesia in children is scarce. Aims: We hypothesized that in children undergoing cardiac catheterization, general anesthesia with a combination of sevoflurane with xenon results in superior hemodynamic stability, compared to sevoflurane alone. Methods: In this prospective, randomized, single‐blinded, controlled clinical trial, children with a median age of 12 [IQR 3‐36] months undergoing diagnostic/interventional cardiac catheterization were randomized to either general anesthesia with 50‐65vol% xenon plus sevoflurane or sevoflurane alone. The primary outcome was the incidence of intraprocedural hemodynamic instability, defined as the occurrence of: (i) a heart rate change >20% from baseline; or (ii) a change in mean arterial blood pressure >20% from baseline; or (iii) the requirement of vasopressors, inotropes, chronotropes, or fluid boluses. Secondary endpoints included recovery characteristics, feasibility criteria, and safety (incidence of emergence agitation and postoperative vomiting. Results: After inclusion of 40 children, the trial was stopped as an a priori planned blinded interim analysis revealed that the overall rate of hemodynamic instability did not differ between groups [100% in both the xenon‐sevoflurane and the sevoflurane group. However, the adjuvant administration of xenon decreased vasopressor requirements, preserved better cerebral oxygen saturation, and resulted in a faster recovery. Xenon anesthesia was feasible (with no differences in the need for rescue anesthetics in both groups). Conclusion: Our observations suggest that combining xenon with sevoflurane in preschool children is safe, feasible, and facilitates hemodynamic management. Larger and adequately powered clinical trials are warranted to investigate the impact of xenon on short‐ and long‐term outcomes in pediatric anesthesia.